Geneflow 2006 - International Plant Genetic Resources Institute (2006)
Geneflow is an annual magazine that contributes to promoting awareness of the importance of the Earth's agricultural biodiversity and the role it plays in improving people's lives and livelihoods. It is produced by Bioversity International, but carries stories from all around the globe, from a wide range of sources including national, regional and international development agencies, non-governmental organizations and research workers.